Evaluation of shear bond strength of composite to porcelain according to surface treatment - Kussano Claudia Minami; Bonfante Gerson; Batista José Gilmar; Pinto João Henrique Nogueira (Fundação Odontológica de Ribeirão Preto, 2003)
This study evaluated the shear bond strength of porcelain/composite using 40 metal + porcelain + composite cylindrical specimens divided into 4 groups, according to porcelain surface treatment: 1) no treatment, 2) mechanical retentions performed with diamond burs, 3) etching with phosphoric acid+silane, and 4) etching with hydrofluoric acid+silane. After being stored in distilled water at room temperature for one week, the specimens were submitted to a shear force (load) and the data were analyzed statistically (ANOVA). The means (in Mpa) of the groups were: 4.71 (group 1); 4.81 (group 2); 11.76 (group 3); 11.07 (group 4). There were no statistically significant differences between groups 1 and 2 and between groups 3 and 4.